GreenPave - Khairil Azman, Masri; Rashida Ferdaus, Rashida; Nur Ezreen, Jasni; Md Shahnewaz, Shoaib; Hasan, Kamrul (2021)
There is no substitute for sustainable and environment friendly roads for globalization and urban development. The prevention of asphalt pavement distresses, various researchers have numerous findings. Kenaf Fiber is mainly use to increase the tensile strength of pavement composite. The fiber asphalt mixture has better resistance cracking degradation under loading. According the definition of the Federal Highway Administration (FHWA), sustainable development should meet three requirements: meeting performance standards, utilizing resource effectively and preserving the ecosystem. Kenaf fiber is ecofriendly and sustainable material.